Sex, politics, and empire : a postcolonial geography - Phillips, Richard, 1965- (Studies in imperialism., 2006)
Thie books investigates controversies surrounding prostitution, homosexuality and the age of consent in the British Empire, and draws conclusions about the importance of sex as a nexus of imperial power relations. It will be of particular interest to academics and students in Geography, History, Postcolonial Criticism and Gender/Sexuality Studies.